Comparasion of self-esteem and aggression between combative and non combative sports of Kashmir Division - Dar, Showkat Ahmad (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
This survey type research aimed to check and compare the self-esteem aggressiveness between combative sports and non- combative sports of Jammu and Kashmir. For knowing the outcome of results A total of sixty 60 sports players, which constitute 30 Combative sport and 30 non-combative sport. The Subjects were selected by purposive sampling. The subjects were considered from the age group between 22-29 years. For the analysis of the self-esteem and aggresssive tendency of the subjects of both the groups I.e. combative sports and non-combative sports group. The Standard questionnaire meant for Self-Esteem by- Dr. Morris Rosenberg's Self-Esteem Scale it has 10 items and the standard questionnaire of aggression constructed by R. L. Bhardwaj scale, were used for data collection and to know the aggression level of individual and team game players of Kashmir University which contains 28 items. The analysis of data was done by using statistical technique ‘t’- test for finding the significance difference of self-esteem aggressive tendency between combative sports and non-combative sports and the level of significance was set at 0.05 levels (p<0.05). After the systematic collection, analysis and interpretation of collected data from all, it is concluded that in comparison between both groups Combative were found with high self-esteem and aggression as compared to non-combative sports players.